Internalized Homophobia and Reduced HIV Testing Among Men Who Have Sex With Men in China. (March 2014) - Pyun, Thomas; Santos, Glenn-Milo; Arreola, Sonya; Do, Tri; Hebert, Pato; Beck, Jack; Makofane, Keletso; Wilson, Patrick A.; Ayala, George
Although previous research has examined barriers and facilitators of HIV testing among men who have sex with men (MSM) in China, few studies have focused on social factors, including homophobia and internalized homophobia. This study utilized data from a global online survey to determine correlates of HIV testing as part of a subanalysis focused on Chinese MSM. Controlling for age, HIV knowledge, number of sexual partners, and other covariates, ever having tested for HIV was significantly correlated with lower internalized homophobia. This study suggests that stigma associated with sexual orientation may serve as a barrier to participation in HIV testing and other health-promoting behaviors.